Geometric Properties for Parabolic and Elliptic PDE's GPPEPDEs, Palinuro, Italy, May 2015 - Gazzola, Filippo; Ishige, Kazuhiro; Nitsch, Carlo; Salani, Paolo (Springer Proceedings in Mathematics & Statistics, 2016)
This book collects recent research papers by respected specialists in the field. It presents advances in the field of geometric properties for parabolic and elliptic partial differential equations, an area that has always attracted great attention. It settles the basic issues (existence, uniqueness, stability and regularity of solutions of initial/boundary value problems) before focusing on the topological and/or geometric aspects. These topics interact with many other areas of research and rely on a wide range of mathematical tools and techniques, both analytic and geometric. The Italian and Japanese mathematical schools have a long history of research on PDEs and have numerous active groups collaborating in the study of the geometric properties of their solutions. .